ПСИХОЛОГО-ПЕ ДАГОГІ ЧНІ ОСНОВИ ЦІЛ ЬОВОГО РОЗВИТКУ ПР ОФЕ СІЙ НИХ ОРІ ЄНТИРІ В В УЧНІВ ЗАГАЛЬНООСВІТ НІХ НАВЧАЛЬНИХ ЗАКЛАДІВ - Pobirchenko, N (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the essence of psychological mechanisms and targeted development of professional orientation in students a comprehensive educational institution. The main directions of the formation of professional orientation in students at different stages of training and development, namely motivational field, cognitive interest, character traits, attitudes towards themselves and others.